Parents' Weekend. Photo 003 - Arkin, Sarah (Tufts Archival Research Center, 2008)
Parents' Weekend. Coffee, Questions, and Answers with Faculty and Students Active in Civic Engagement Research. Moderated by Dean of Undergraduate Education Jim Glaser, with participants Professor Lynne Pepall, chair, Department of Economics; Tim Ryan, LA '06; and Michael DeBartolo, LA '06. In the Alumnae Lounge.